Gene Therapy Knowledge and Attitude Among Healthcare Professionals: A Cross-Sectional Study - AlRasheed, Maha M.; AlAli, Hatoon; Alsuwaid, Abdulrahman F.; Khalaf, Suhail; Ata, Sondus I.; BinDhim, Nasser F.; Bakheet, Dana; Khurshid, Fowad; Alhawassi, Tariq M. (Frontiers in Public Health, 2021)
This study aimed to assess healthcare professionals' knowledge, attitudes, and concerns toward gene therapy in Saudi Arabia. We conducted an online cross-sectional survey via convenience sampling during the period from December 2018 to March 2019. A total of 419 (358 pharmacists and 61 physicians) responded to our questionnaire. Three hundred and nine (73.7%) were male, and the mean (±SD) age of 32.0 ± 7.7 years. The mean knowledge scores of all participants, pharmacists, and physicians were 3.8 ± 1.9, 3.8 ± 1.9, and 3.7 ± 1.9, respectively (P = 0.73). Higher knowledge score was associated with younger age (Coefficient: −0.03; P = 0.02), male (Coefficient: 0.57; P = 0.01), master's degree (Coefficient: 0.93; P = 0.003) and Ph.D. holders (Coefficient: 1.10; P = 0.01), and participants graduated from Canada (Coefficient: 2.10; P = 0.01).Moreover, about half of the respondents (55%) were concerned about gene therapy, and genetics training at college was considered the best gene therapy education method by 69.4%. Attitude score was not significantly associated with the profession (P = 0.88) but positively correlated with the knowledge score (rho= 0.4; P < 0.001). In conclusion, pharmacists and physicians showed limited knowledge with a positive attitude toward gene therapy. Therefore, educational programs on gene therapy need to be considered, focusing primarily on the safety, and social acceptance of such new therapeutic management.